Piezoelectric polymer nanofibers for pressure sensors and its applications in human activity monitoring - Zhu, Minmin (2021)
Miniaturized, wearable and self-powered sensors are crucial for applications in artificial intelligence, robotics, healthcare, as well as communication devices. In particular, piezoelectric polymer-based sensing system has the advantages of light weight, large piezoelectricity and mechanical flexibility, offering great opportunities in flexible and stretchable electronic devices. Herein, free-standing large-size nanofiber (NF) membranes have been fabricated by electrospinning technique. Our results show that the as-synthesized P(VDF-TrFE) NFs are pure β-phase and exhibits excellent mechanical and thermal properties. Besides having high sensitivity and operation stability, the fibrous sensor can generate remarkable electrical signals from the applied pressure, with an output voltage of 18.1 V, output current of 0.177 μA, and power density of 22.9 μW/cm2. Moreover, such sensors also produce significant electric performances of up to a few voltages under human mechanical stress, thereby allowing for the monitoring of biomechanical movement of the human foot, elbow, and finger. Our study sheds insights into piezoelectric polymers for flexible self-power sensing electronics and wearable devices.